Reconstruction of Ipsilateral Femoral and Tibial Bone Defect by 3D Printed Porous Scaffold Without Bone Graft: A Case Report. Issue 1 (January 2022) - Hou, Guojin; Liu, Bingchuan; Tian, Yun; Liu, Zhongjun; Zhou, Fang
Abstract : Case: This study reported the case of a 42-year-old woman with traumatic ipsilateral critical bone defect of right femur and tibia after a motor accident. Three-dimensional (3D) printed porous titanium scaffolds were innovatively used to reconstruct this challenging situation. The initial stability was safe enough for early exercise and partial weight bearing. The 26-month follow-up showed osseous integration of the prosthesis-bone interface with short-term satisfactory clinical result. Conclusion: The custom-designed 3D-printed porous scaffold has the potential to become an effective option for reconstructing the segmental irregular-shaped bone defect.